Knowing one's values through courtship a qualitative study on young adult's social and cultural values during verbal and non-verbal courtship - Foronda, Catherine A. 1978- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Interpersonal communication unpredictably varied from situation to situation. The surrounding context on which the verbal or nonverbal interaction took place deemed the language that was eventually employed. External factors like power relations and alternate perceptions might have influenced the subsequent interpretation of messages. The focus of the research is to analyze the verbal and nonverbal exchange between individuals in the courtship context. How meanings were labeled on touch (haptics), how the level of distance (proxemics) was understood by both parties, and how swapped messages through smiles and stares (kinesics) were taken to signify specific traits were attempted to be explained. The pattern that the male initiated personal topics and verbal techniques were also discussed. Social and cultural values were then identified through the working rules observed and the existing norm maintained by both parties during a face-to-face interaction. The preserved and emerging values were later on enumerated. In some instances, a comparison between traditional and contemporary courtship was inevitable.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Courtship -- Philippines -- Manners and customs; Courtship -- Philippines -- Interpersonal communication and culture